RURAL AREAS OF POLAND AS THE BENEFICIARY OF EUROPEAN UNION FUNDING 2007−2013(15) FOR CULTURAL PROJECTS - Powęska, Halina (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The paper presents the issues relating to the use of EU funds for cultural heritage projects in rural areas in Poland in the years 2007–2015. The study examines the structure of the funding of EU cultural heritage projects by the purpose of their implementation including revaluation of cultural heritage objects, creation and development of a new tourism product, renovation of sports and recreation infrastructure, promotion and other issues. The spatial analysis was carried out at the level of voivodships. The survey was conducted using the database of the National Information System of the Ministry of Infrastructure and Development of the Republic of Poland (NIS SIMIK 07-13) as at 31 December 2015. In the years 2007–2015, in both rural areas and rural districts, in the case of those projects which were aimed at developing infrastructure and restoring cultural heritage assets, while projects thematically related to the creation of a new tourism product and promotion were of lesser importance. However, the highest grants from EU sources were provided for projects thematically related to the reconstruction of cultural heritage and creation of tourism products, which shows that the activities aimed at preservation of cultural heritage and support for local entrepreneurship are of particular significance to European entities.